Biographical dictionary of Christian theologians - Carey, Patrick W., 1940-; Lienhard, Joseph T. (Greenwood Press, 2000)
The last 20 centuries of Christian history have witnessed the emergence of numerous theological traditions. This reference provides alphabetically arranged entries for more than 450 Christian theologians. Included are entries for those individuals whose work was primarily in systematic and spiritual theology, or who were church historians chiefly concerned with theological matters. Whenever possible, each entry provides basic biographical information, a brief account of the theologian's education and career, and a summary of the person's most important contributions to theology. The entries end with bibliographies of primary and secondary sources, while the volume concludes with a selected, general bibliography.